UMP Ulul Albab Tahfiz Certification Programme to produce hafiz technocrat - UMP, PNC (2019)
The Ulul Albab Tahfiz Certification Programme introduced by Universiti Malaysia Pahang (UMP) aims to produce professionals, technocrats and entrepreneurs who are also hafiz.